(untitled) (Interdisciplinary Studies Journal, 2024)
This article presentes the necessity to discuss and to highlight the differents adolescent experiences in the school setting, in addition to desing the intersectionality like concept and pratice applied to education. A narrative literature review was made using descriptors like diversity in schools, intersectionality, adolescence, construction of identity sense and school practices. The present review rated how to discuss intersectionality and diversity in school environment is foundational to improve equal opportunities and combating preconceived ideas. Educators need to be prepared and attend, inclusively, the studentes requirements, allowing the diversity of identity expression and contributing for a society more tolerant and equal.